Sam Wu is not afraid of spiders - Tsang, Katie, 1987-; Tsang, Kevin (Tsang, Katie, 1987- Sam Wu is not afraid., 2020)
"Sam Wu is NOT afraid of anything. Well, maybe some things--like ghosts, sharks... and the dark's pretty scary, too. And now he has something new to worry about: Tulip, the big, hairy pet tarantula that lives in the sixth-grade science lab and is coming to visit his class. But Sam can't let anyone know. So when Tulip disappears from her cage, Sam decides it's up to him and his friends to step up, save the school from the eight-legged escapee... and prove, once again, that he's no scaredy cat!" --